2015
DOI: 10.1016/j.techsoc.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the attitudes on entrepreneurial universities: The case of Croatian and Spanish universities

Abstract: The objective of this paper is to present evidence that there are different types of supportive faculty members. We conducted a case study on a sample of Croatian and Spanish universities by using an already tested ENTRE-U scale for measuring the faculty members' attitudes. These two scenarios are quite different in terms of their innovation systems, economic context and university system. We tested and found no evidence of any statistically significant difference due to the country. These two facts suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 56 publications
(50 reference statements)
1
27
0
1
Order By: Relevance
“…It is because of a possible mismatch between official declarations and the reality in research teams. Dabic et al (2015) studied other moderately innovative economies and found that a large group of professors felt that their university had a very low degree of entrepreneurial orientation, even though they really supported the idea of an entrepreneurial university. Anyway, coming back to the discussed study, the performance self-assessments present relatively high levels of satisfaction and strong belief in own experience with open innovation-related tools.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is because of a possible mismatch between official declarations and the reality in research teams. Dabic et al (2015) studied other moderately innovative economies and found that a large group of professors felt that their university had a very low degree of entrepreneurial orientation, even though they really supported the idea of an entrepreneurial university. Anyway, coming back to the discussed study, the performance self-assessments present relatively high levels of satisfaction and strong belief in own experience with open innovation-related tools.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The interest in the application of the scale has grown over time so that it is currently a unique method for measuring entrepreneurial orientation in universities. The researchers who have used it in their studies have adjusted the scale and improved its practical application in the process [33,34,36]. The authors of this paper have no indication that such a scale has been used in other developing countries, which inspired them to validate it at state universities in the Republic of Serbia.…”
Section: Methods and Datamentioning
confidence: 99%
“…Universities need to adopt the entrepreneurship as their purpose and establish a culture in which every employee is dedicated to accomplish that purpose [33]. The entrepreneurial university is a university in which research groups are behaving like quasi-firms [34], while leaders of those groups act as entrepreneurs, or executives, as Ceptureanu et al (2017) call them in their paper [15]. During their transition to entrepreneurial institutions, universities pass through different phases, similar to a business life-cycle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First of all, entrepreneurial universities can stimulate contacts between young entrepreneurs, managers and entrepreneurs that have already driven internationalisation processes, thus stimulating direct knowledge transfer between entrepreneurs (Dabic et al, 2015). Secondly, since an entrepreneurial university is usually many potential capital providers and investors, as well as with other firms (Gaff et al, 2012), it could help young entrepreneurs in creating a transnational network usable to implement a semi-classical process of internationalisation.…”
Section: Entrepreneurial Universities and The Internationalisation Phmentioning
confidence: 99%